2018
DOI: 10.1016/j.ijnurstu.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Safewards model in public mental health facilities: A qualitative evaluation of staff perceptions

Abstract: This study highlights some difficulties with implementing Safewards and maintaining fidelity of the Safewards interventions in busy acute inpatient wards. Although these findings are from a qualitative study consisting of only 15 staff, our results indicate that efforts to implement Safewards need to address challenges faced by staff in engaging with the interventions, ensure buy-in from management, ensure adequate training and support during implementation and review training materials to ensure they fit with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
145
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(158 citation statements)
references
References 24 publications
7
145
1
5
Order By: Relevance
“…The fact that results regarding frequency and duration of coercive measures differ substantially between wards underlines these aspects. This phenomenon is well-known from previous reports where engagement with the Safewards Model varies between wards and even within wards (2). Reasons discussed for those differences on the level of wards are number, education, resilience, professional self-conception, professional experience, stress level, and personality of employees (59).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The fact that results regarding frequency and duration of coercive measures differ substantially between wards underlines these aspects. This phenomenon is well-known from previous reports where engagement with the Safewards Model varies between wards and even within wards (2). Reasons discussed for those differences on the level of wards are number, education, resilience, professional self-conception, professional experience, stress level, and personality of employees (59).…”
Section: Discussionsupporting
confidence: 65%
“…Managing conflict and violent situations such as self-harm, drug abuse, physical aggression, verbal abuse, or aggressive behavior towards others is part of acute inpatient psychiatric care. It has become a major focus for staff interventions in such units (1, 2). Coercive interventions are often used to contain such situations, even though they may cause harm to patients and staff (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these components were recommended by patients included in the reviewed studies and/or identified as factors that improved their experience of detention. Difficulties implementing the safewards model have, however, included high staff turnover, 87 which patients in this review also highlighted as a barrier to building trusting relationships.…”
Section: Discussionmentioning
confidence: 98%
“…A further two evaluated the TeamSTEPPS (Team Strategies and Tools to Enhance Performance and Patient Safety) programme268 269 and both found significant clinical benefits in reducing seclusion and improving team functioning. One paper looked at the barriers and facilitators to implementing a Safewards intervention 270. With regard to policy, eight studies concerned safety policies related to: observation,271 272 risk assessment,273 274 treatment,275 safeguarding,276 security277 and ergonomic improvement 278.…”
Section: Resultsmentioning
confidence: 99%